Design, Synthesis and Anticancer Activity of New Benzofuran‐Chalcone Hybrids and Their Water Soluble Sodium Salts. Issue 9 (28th February 2023) - Cinar‐Asa, Sibel; Coskun, Demet; Akgun, Oguzhan; Akgun, Halime; Fatih Coskun, Mehmet; Ari, Ferda
Abstract: In this study, firstly, 1‐(7‐ethoxy‐1‐benzofuran‐2‐yl) ethanone and 1, 1'‐(7‐ethoxy‐1‐benzofuran‐2, 4‐diyl)diethanone were synthesized for the starting reagent purposes. The synthesized benzofuran‐chalcone salts were soluble in water at room temperature. Structural analysis of the synthesized compounds was characterized by elemental analysis, FT‐IR and NMR spectroscopy techniques. The anticancer activities of the compounds were determined by SRB viability assay in human lung cancer (A549, H1299) and breast cancer (MCF‐7, MDA‐MB‐231) cell lines. Findings for apoptosis were determined by flow cytometry analysis and the PARP‐ELISA method. The results of the in vitro SRB analysis of the compounds showed that some of the chalcone hybrids were very effective on both types of cancer in a dose and time‐dependent manner. Treatment of all cancer cell types with these hybrids resulted in a significant increase in the percentage of early and mainly late apoptotic cells, demonstrating their apoptosis‐inducing effects via the Caspase 3/7 Activity. Abstract : Chalcone compounds are one of the non‐heterocyclic C ring members of the flavonoid family. It is known that chalcones are found in edible plants and fruits in nature and are very beneficial compounds for health. Although there are many studies on chalcones, there are very few studies on chalcones containing benzofuran. In this study, it was investigated whether new chalcone derivative compounds carrying benzofuran ring have anti‐cancer effects on some cancer cell lines, thus their potential as a new chemotherapeutic agent targeting only cancer cells.